Bioaerosols in the atmospheric environment of oil exploitation sites: spatial and temporal distribution, sources, influencing factors, health risks, and reduction efficiency of masks - Hongjie Yang; Shen He; Zongting Yao; Hao Li; Qihao Feng; Simin Huang; Zhen Chen; Jiasheng Ni; Zhishu Liang (Environmental Pollution, 2026)

Molecular-weight modulation improves the physicochemical properties and in vitro release behavior of spray-dried Agaricus bisporus polysaccharide microcapsules - Simin Feng; Jiaxin Dai; Tingxuan Zong; Manyu Zhang; Pu Yang; Yuyan Wang; Kseniya Hileuskaya; Yizhen Xie; Ping Shao (Food Bioscience, 2026)

Corrigendum to “Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties” [Food Res. Int. 214 (2025) 116601] - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2026)

Enhancement of ursolic acid (UA), an active ingredient in hawthorn, on the uptake and metabolism of 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (THSG) derived from Polygonum multiflorum - Runlu Li; Simin Ren; Yunhong Zhao; Ni An; Jingwu Song; Feng Guan; Jian Ge (Food Research International, 2026)

Green and sustainable dual-pathway strategies for high-efficiency photoconversion of ergosterol to vitamin D₂ from agaricus bisporus - Jiahao Yu; Yan Tang; Yang Lin; Simin Feng; Mofei Shen; Ping Shao (Food Chemistry, 2026)

Multiscale mechanisms and challenges of chiral nanomaterials in cancer immunotherapy - Zhusheng Huang; Hao Zhou; Shaoyin Zhang; Simin Song; Zhongcheng Ke; Chuanliang Feng; Jianyuan Tang; Yunlu Dai (Science Bulletin, 2026)

Chloride source dynamics under dry–wet conditions in a watershed with imbalanced chloride input–output: Insights from tracer-aided modeling - Jianfeng Gou; Simin Qu; Wenjie Liu; Chong Wei; Xueliang Feng (Journal of Hydrology, 2026)

Combined toxicity of nanoplastics and microcystin-LR to sulfate-reducing bacteria and the underlying mechanisms - Wei Du; Hao Wu; Simin Wang; Lin Cao; Yanmei Feng; Xiang Wu (Environmental Pollution, 2026)

AI-assisted discovery of dual antioxidant and ACE-inhibitory peptides from Hericium erinaceus - Rongheng Chen; Jiahao Yu; Simin Feng; Ping Shao (Food Chemistry, 2026)

Plant sterol ester-modified naringenin liposomes: A novel strategy for effectively penetrating the mucus barrier - Liuqing Yang; Jingjian Liu; Shuqi Liang; Baihui Guo; Gaodan Liu; Tarun Belwal; Simin Feng (Food Research International, 2025)

Improved water solubility of myofibrillar protein through enzymatic deamidation and glycosylation: Insights into molecular behavior of myosin - Miao Feng; Yuxin Huang; Xuefei Wang; Simin Zheng; Qian Chen; Baohua Kong; Haotian Liu; Chao Zhang (Food Chemistry, 2025)

Study on the effects of phosphoric acid-modified biochar on the adsorption behavior and bioavailability of oxytetracycline in saline-alkali soils - Runfang Yao; Shiqi Tao; Yuyun Chen; Zengyu Liu; Simin Feng (Environmental Geochemistry and Health, 2025)

Activation of the cGAS-STING pathway in monocytes exacerbates pulmonary fibrosis induced by paraquat poisoning - Yangyang Sun; Zheming Yuan; Weidong Li; Xueyang Lin; Chen Yang; Yufeng Yang; Hui Miao; Shengran Wang; Ziqi Cui; Zhenghao Bao; Simin Lang; Weiqiang Sun; et al. (Toxicology and Applied Pharmacology, 2025)

Naringenin-loaded Flammulina velutipes chitin-glucan complexes gel system: structural modulation and dual lipid-lowering mechanisms - Simin Feng; Shuqi Liang; Jianyu Yang; Jiahao Yu; Yang Lin; Yizhen Xie; Peilong Sun; Ping Shao (Food Chemistry, 2025)

Scenario-based simulation of ecosystem service supply and demand in China's Yangtze River Economic Belt - Lanqing Zhang; Fei Feng; Huihui Huang; Yuan Cao; Simin Jiang; Wenlei Shi; Haoyuan Lv; Chenyang Xu; Giovanni Sanesi; Raffaele Lafortezza (Environmental Research, 2025)

Enhancing sunlight-driven photocatalysis of Ag/AgCl@MOF-808 heterojunction via synergistic effects of plasmonic Ag QDs and heterostructure - Hongkun Luo; Menghao Feng; Simin Zheng; Weisi Wang; Xiongjian Li (Journal of Environmental Chemical Engineering, 2025)

Limonene-loaded nanostructured lipid carriers incorporated in hydrogels: Enhanced acid stability and controlled release properties - Simin Feng; Yitong Tian; Jiahao Yu; Yang Lin; Alan Giovanini de Oliveira Sartori; Ping Shao (Food Research International, 2025)

Enhancing water security in lake basins through geographic intelligence technology - Yong Ge; Li Zhang; Yi Han; Die Zhang; Wenjing Yang; Lian Feng; Jinwei Dong; Shuping Wang; Simin Peng; Chaoyang Fang (Science Bulletin, 2025)

Studies on the effect of microplastics on the adsorption and migration of Phenanthrene in river sediment - Simin Feng; Runfang Yao; ·Yuyun Chen; Hongli Zhang (Environmental Geochemistry and Health, 2025)

The Impact of Microplastics on Adsorption of Chlorophenols by River-Suspended Sediments - Shiqi Tao; Simin Feng; Yuyun Chen; Ting Duan; Zengyu Liu; Ling Li; Rongrong Yun; Chayma Chilouch (Environmental Management, 2025)

Iron‐Driven Fast Decomposition of Soil Carbon Under Periodic Anoxia - Ting Liu; Xin Wang; Simin Wang; Erxiong Zhu; Steven J. Hall; Xiaojuan Feng (Global Change Biology, 2025)
Soil organic carbon (SOC) decomposition underpins soil‐atmosphere carbon exchange and is regulated by climate change‐mediated variations in soil redox conditions. Periodic anoxia, commonly occurring following precipitation, soil flooding, and erosion events, is assumed to preserve SOC. Yet, water saturation may also increase SOC decomposition relative to unsaturated conditions, and contradictory findings among previous studies remain unexplained. Here, using incubation experiments on 20 soils collected across a 24° latitude gradient in China, we show that 70% of the soils showed a higher or similar anoxic decomposition rate of SOC compared to the oxic treatment, indicating fast SOC loss under relatively short anoxia. Methane production was far lower than CO 2 due to the presence of alternative terminal electron acceptors (TEAs). Variation in alternative TEAs and microbial community shows that fast anoxic decomposition was primarily driven by iron (Fe) reduction, which accounted for up to 90% of anoxic CO 2 production. Meanwhile, positive relationships among water‐extractable organic carbon (OC), hydrochloric acid‐extractable ferrous Fe, relative abundance of Fe‐reducing prokaryotes, and the SOC decomposition rate suggest the release of readily metabolized substrates following Fe reduction. This release provided substrates for anoxic metabolism and potentially led to the loss of OC protected by Fe (Fe‐bound OC; a slow‐cycling OC pool under oxic conditions). Mass balance calculation confirms that Fe‐bound OC loss was mostly similar to elevated anoxic SOC decomposition in magnitude, and random forest modeling indicates that soils rich in reducible Fe, SOC, and Fe‐reducing prokaryotes most likely experience elevated SOC decomposition under periodic anoxia. Overall, our findings demonstrate that fast anoxic decomposition of SOC is a potentially important pathway that may stimulate SOC loss under climate change‐mediated intense hydrologic regimes, particularly for soils rich in reducible Fe and SOC.

Household waste-specific ambient air shows greater inhalable antimicrobial resistance risks in densely populated communities - Zhipeng Zheng; Wenhui Ji; Xiao Wang; Xueting Wang; Simin Dai; Zhaowen Zhang; Yinghua Zhang; Xiaoyan Wang; Shen Cao; Min Chen; Bing Xie; Jun Feng; et al. (Waste Management, 2025)

Experimental treatment of pickled vegetable wastewater by electrofenton method based on modified PbO2 electrode - Likun Huang; Jingyi Zhang; Guangzhi Wang; Dandan Wang; Zhe Li; Simin Zhou; Xinyi Di; Xinyu Feng (Process Safety and Environmental Protection, 2025)

Insight into aroma dynamic changes during the whole manufacturing process of smoked Lapsang Souchong tea - Weiying Su; Zhibin Liu; Simin Huang; Daoliang Wang; Xiaoxiao Feng; Yuan Liu; Li Ni (Food Chemistry, 2025)

Simultaneously enhancing the EMI shielding performances and mechanical properties of structure–function integrated CF/PEEK composites via chopped ultra-thin carbon fiber tapes and interfacial engineering with MXene - Simin Zhang; Jinze Cui; Xingwen Kuang; Mingbin Lai; Yutai Luo; Feng Bao; Jiali Yu; Caizhen Zhu; Jian Xu; Huichao Liu (Chemical Engineering Journal, 2024)

Soy conglycinin amyloid fibril and chitosan complex scaffold for cultivated meat application - Simin Feng; Siqing Dai; Zhengxun Wei; Jing Wang; Ning Xiang; Ping Shao (Food Hydrocolloids, 2024)

Identification and validation of two major QTL for grain number per spike on chromosomes 2B and 2D in bread wheat (Triticum aestivum L.) - Simin Liao; Zhibin Xu; Xiaoli Fan; Qiang Zhou; Xiaofeng Liu; Cheng Jiang; Fang Ma; Yanlin Wang; Tao Wang; Bo Feng (Theoretical and Applied Genetics, 2024)

Novel synthesis of CuFe2O4/g-C3N4 based on microwave ferromagnetic resonance effect for the thorough removal of TC in mariculture wastewater under natural sunlight - Xiyu Sun; Huanzhang Feng; Guangzhi Wang; Likun Huang; Dongdong Wang; Simin Zhou; Rui Zhao (Chemical Engineering Journal, 2024)

Potential retention of dissolved organic matter by soil minerals during wetland water-table fluctuations - Simin Wang; Ting Liu; Erxiong Zhu; Chen He; Quan Shi; Xiaojuan Feng (Water Research, 2024)

Ecological transformation is the key to improve ecosystem health for resource-exhausted cities: A case study in China based on future development scenarios - Simin Jiang; Fei Feng; Xinna Zhang; Chengyang Xu; Baoquan Jia; Raffaele Lafortezza (Science of The Total Environment, 2024)

Enhancing acid stability of citral through internal structure modulation in nanostructured lipid carriers with solid lipids and phospholipids - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Research International, 2024)

Multi-objective optimization of water electrolysis based on coupling model of electrochemistry and multiphase flow - Xudong Duan; Juan Xiao; Xiaocheng Peng; Shuwen Feng; Simin Wang; Jian Wen (Journal of Environmental Chemical Engineering, 2023)

Encapsulation and release of citral using nanostructured lipid carriers: A study on the impact of different preparation methods - Simin Feng; Jialu Sheng; Jiahao Yu; Yang Lin; Ping Shao (Food Bioscience, 2023)

Enhanced microbial contribution to mineral-associated organic carbon accrual in drained wetlands: Beyond direct lignin-iron interactions - Chengzhu Liu; Simin Wang; Yunpeng Zhao; Ya Wang; Yiyun Wang; Erxiong Zhu; Juan Jia; Zongguang Liu; Jin-Sheng He; Xiaojuan Feng (Soil Biology and Biochemistry, 2023)

Tracing global N2O emission mitigation strategies through trade networks - Kemeng Liu; Rong Ma; Kejia Yan; Bo Zhang; Simin Xu; Cuiyang Feng (Journal of Environmental Management, 2023)

Plant influences on soil microbial carbon pump efficiency - Xiaojuan Feng; Simin Wang (Global Change Biology, 2023)
Microbe‐mediated carbon transformation plays an important role in soil carbon sequestration, which is considered to be one of the key strategies to achieve carbon neutrality in the long term. Assessing the efficiency of microbial necromass accumulation relative to plant carbon input or microbial respiration will help to identify ways to promote soil carbon sequestration from an ecosystem perspective.

Identification and validation of quantitative trait loci for fertile spikelet number per spike and grain number per fertile spikelet in bread wheat (Triticum aestivum L.) - Cheng Jiang; Zhibin Xu; Xiaoli Fan; Qiang Zhou; Guangsi Ji; Liangen Chen; Qin Yu; Simin Liao; Yun Zhao; Bo Feng; Tao Wang (Theoretical and Applied Genetics, 2023)

Fabrication of high strength cold-set sodium alginate/whey protein nanofiber double network hydrogels and their interaction with curcumin - Sijie Wu; Lu Wang; Yingying Zhao; Bilian Chen; Dan Qiu; Peilong Sun; Ping Shao; Simin Feng (Food Research International, 2023)

Microwave-assisted co-precipitation preparation of CuFe2O4 photo-Fenton degradation tetracycline: Characterization, efficacy, stability in complex water quality and mechanism - Xiyu Sun; Guangzhi Wang; Likun Huang; Huanzhang Feng; Simin Zhou; Rui Zhao; Dongdong Wang; Zhe Li (Journal of Environmental Chemical Engineering, 2023)

Deep eutectic solvent on extraction of flavonoid glycosides from Dendrobium officinale and rapid identification with UPLC-triple-TOF/MS - Minghui Sui; Simin Feng; Gaodan Liu; Bilian Chen; Zhenhao Li; Ping Shao (Food Chemistry, 2023)

Classifying motion states of AUV based on graph representation for multivariate time series - Chen Feng; Shuang Gao; Simin Chen; Zhongke Gao; Celso Grebogi (Ocean Engineering, 2023)

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

Assessing the total factor productivity growth decomposition: the transformation of economic growth momentum and policy choice in China - Feng Luo; Feng Chen; Dandan Yang; Simin Yang (Environmental Science and Pollution Research, 2022)

A review on chemical and physical modifications of phytosterols and their influence on bioavailability and safety - Simin Feng; Liling Wang; Ping Shao; Peilong Sun; Chung S. Yang (Critical Reviews in Food Science and Nutrition, 2022)

Effects of Shear Stress and Salinity Stratification on Floc Size Distribution During the Dry Season in the Modaomen Estuary of the Pearl River - Jie Huang; Simin Wang; Xinran Li; Rongyao Xie; Jianxiong Sun; Benwei Shi; Feng Liu; Huayang Cai; Qingshu Yang; Zhaoyong Zheng (Frontiers in Marine Science, 2022)
The floc size distribution of fine cohesive sediments in estuaries varies spatiotemporally within assorted physical, chemical, and biological factors. However, the distribution of different floc fractions that are affected by shear stress and salinity stratification has not yet been thoroughly investigated. This study intends to clarify the floc size distribution within the influences of turbulent shear rate and salinity stratification, and the implications for the flocculation process during the dry season in the Modaomen Estuary of the Pearl River. The decomposition of multimodal floc size distributions (FSDs) indicates that the floc fractions were composed of macroflocs (Macro), microflocs (Micro), Flocculi, and primary particles (Pp). Macro generally existed among the upper and middle layers, but smaller flocs, i.e., Micro, Flocculi, and Pp, were mostly concentrated in the bottom layer. The results agreed that the flocculation and deflocculation processes were dominant in the upper and bottom layers, respectively. In response to strong turbulent shear rates, FSDs in the bottom layer skewed toward small sizes and had a dual-peak tendency with frequent floc exchanges between Pp and Micro, then being Pp-dominant but converting to Micro when turbulent shear rates decreased. With impeded vertical mixing by salinity stratification, the FSDs in the upper or middle layers skewed toward a larger particle size with single peaks and lack of exchange among different floc fractions, leading to Macro dominance with a larger volume concentration and median size. In addition, turbulence mixing dramatically interfered with the good mixing of floc fractions amidst the vertical water column, with a low-salinity condition greatly affecting the formation of Macro in the bottom layer within proper turbulent shear rates. This study explores the effects of shear stress and salinity stratification on the flocculation process in the Modaomen Estuary, which contributes to a better understanding of sediment movement in a complex estuarine environment.

Preparation of sludge-based materials and their environmentally friendly applications in wastewater treatment by heterogeneous oxidation technology - Xiyu Sun; Guangzhi Wang; Huanzhang Feng; Xinyi Miao; Simin Zhou; Dongdong Wang; Likun Huang; Kun Wang (Environmental Science and Pollution Research, 2022)

Gene expression profiles in the brain of phenylketonuria mouse model reversed by the low phenylalanine diet therapy - Sha Hong; Tianwen Zhu; Simin Zheng; Xia Zhan; Feng Xu; Xuefan Gu; Lili Liang (Metabolic Brain Disease, 2021)

Study on influence factors of treating landfill leachate by ultraviolet-activated persulfate system - Guangzhi Wang; Simin Zhou; Dongdong Wang; Lina Feng; Yuanyuan Xu; Likun Huang (Environmental Science and Pollution Research, 2021)

Paleoclimatic proxies from global closed basins and the possible beginning of Anthropocene - Yu Li; Qin Han; Lu Hao; Xinzhong Zhang; Dawei Chen; Yuxin Zhang; Lingmei Xu; Wangting Ye; Simin Peng; Yichan Li; Zhuowen Feng; Hebin Liu (Journal of Geographical Sciences, 2021)

Warmth is more influential than competence: an fMRI repetition suppression study - Mingzhu Li; Zifeng Mai; Simin Wang; Tingyong Feng; Frank Van Overwalle; Ning Ma (Brain Imaging and Behavior, 2021)

Correction to: Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Fine mapping and identification of the fuzzless gene GaFzl in DPL972 (Gossypium arboreum) - Xiaoxu Feng; Hailiang Cheng; Dongyun Zuo; Youping Zhang; Qiaolian Wang; Ke Liu; Javaria Ashraf; Qiuhong Yang; Simin Li; Xiaoqin Chen; Guoli Song (Theoretical and Applied Genetics, 2019)

Impact of depositional environment and diagenesis on the Upper Triassic Xujiahe tight-sand reservoir in Guang’an area, Central Sichuan Basin, SW China - Dan He; Xinguo Duan; Simin Li; Bo Zhou; Honghui Wang; Yong Heng; Shuang Feng (Carbonates and Evaporites, 2019)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)